A novel thermo-thickening viscosity modifying admixture to improve settlement stability of cement slurry under high temperatures. (9th August 2021) - Chen, Xin; Wang, Chengwen; Xue, Yucheng; Chen, Zehua; Jin, Jianzhou; Wang, Ruihe
Highlights: HTP compensates for viscosity reduction of cement slurry due to temperature rises. HTP improves the settlement stability of oil well cement slurry systems. HTP contributes to the uniform micromorphology of hardened cement paste. Abstract: The viscosity of cement slurry decreases when the temperature rises, resulting in bleeding and sedimentation issues caused by high temperatures. The available viscosity modifying admixtures (VMAs) usually thicken cement slurry under low temperatures but their performances deteriorate under higher temperatures. This study proposes a novel thermo-thickening VMA (i.e., a thermo-thickening polymer with strong hydrophobicity, HTP); its thickening ability will become stronger with an increase in temperature. HTP helps to compensate for the consecutive viscosity reduction of cement slurry due to temperature increases and yields a constant-consistency cement slurry over a wide temperature range (up to 165 °C). Most importantly, HTP is able to slash the bleeding water exuded from cement slurry and eliminate the compressive-strength/density differences among the upper-middle-lower hardened cement paste segments, resulting in a significant improvement in the settlement stability of cement slurry. Microscopic observations reveal that the HTP molecules may fully stretch in the cement slurry and integrate with cement hydration products, contributing to the uniform micromorphology of hardened cement paste. The novel thermo-thickening VMA imposes a limited impact on the compressive strength, fluid loss and thickening time of cement slurry and is very compatible with various cement additives. Finally, the high-temperature high-density cement slurry system containing HTP exhibits a constant consistency until rapid setting behavior, which suggests that it has good potential for field applications.